DOCTRINE MODEL OF CRIMINOLOGY STRATEGY ENSURING ROAD TRAFFIC SAFETY IN UKRAINE (Bulletin of criminological association of Ukraine, 2023)
The article is devoted to the development of a doctrinal model of a criminological strategy for ensuring traffic safety and transport operation. Three main components of such a model are identified, described and explained: value-orienting, structural-functional and support component. The strategic goals, main directions and key measures of criminological security of traffic and operation of transport are described. Their list and configuration are open, can and should be supplemented in order to achieve the goal of effective countermeasures against criminal offenses against traffic safety and transport operation. The connection of this process with the implementation of the tasks of transitional justice in Ukraine is emphasized.
Keywords: traffic safety; transport operation; criminal offenses; determination; crime prevention; strategy; criminological support; transitional justice